3-L Split-dose is Superior to 2-L Polyethylene Glycol in Bowel Cleansing in Chinese Population. Issue 4 (January 2015) - Zhang, Shenghong; Li, Minrui; Zhao, Yagang; Lv, Tao; Shu, Qing; Zhi, Fachao; Cui, Yi; Chen, Minhu; Keuchel., Martin
<x xml:space="preserve">Abstract</x> Abstract Large volume (4 L) of polyethylene glycol (PEG) solution would ensure a better quality of bowel cleansing but might be poorly tolerated. Due to the smaller body size, lower body weight, and different diet habits, the large volume of 4-L PEG might be poorly tolerated by the Chinese population. In view of this, a balance should be made between the volume and effectiveness. This study aimed to compare the effectiveness, compliance, and safety between 3-L split-dose and 2-L PEG in Chinese population. Consecutive patients scheduled for colonoscopy were recruited from 5 tertiary medical centers in South China between April and July, 2014. Patients were prospectively randomized into 2 groups: 3-L split-dose PEG (3L-group) and 2 L PEG (2L-group). The primary endpoint was bowel cleansing and was defined according to Ottawa Bowel Preparation Scale (OBPS). The safety and compliance were also evaluated. A total of 318 patients were included in the analysis. The mean total OBPS score was significantly higher in 2L-group than in 3L-group (4.4 ± 2.7 vs 2.9 ± 2.4, P < 0.001). Both the intention-to-treat and per-protocol analysis found that rates of successful and excellent bowel preparation were much higher in 3L-group (89.9% and 78.0%) than 2L-group (79.2% and 48.4%), respectively (P < 0.001). The average cecum intubation time was significantly shorter in 3L-group (8.2 ± 3.7 min) than in 2L-group (10.3 ± 4.2 min) (P = 0.04). Adenoma detection rate in right colon was slightly higher in 3L-group than in 2L-group (17.6% vs 12.6%, P = 0.21). The safety and compliance including the taste, smell, and dosage of PEG were similar between 2 groups (P > 0.05). 3-L split-dose PEG is superior to 2-L PEG by better bowel cleansing, improved safety and compliance, shorter cecum intubation time, and potentially higher adenoma detection rate in rightward colon in Chinese population.